(untitled) (Revista LIDER, 2020)
In the last decades, there has been a greater influence of industrial districts in regional science, seen as key factors of growth and capital accumulation. This phenomenon started in the crisis of the fordist production model, that has allowed pheripherical territories, often especialized in artisan manufacturing, to systematically gain markets and become winners in an increasingly globalized economy. For third world countries, these new industrial configurations have become a new paradigm to imitate, seen as a valid instrument to surpass the lack of exports and external dependency. The present work analyzes the attempt of conformation of an industrial district in the Southwest of Buenos Aires Province (Argentina).